Development of New or Enlarging MRI Lesions Outside of Clinical Attacks in MOG-Antibody-Associated Disease. (5th December 2022) - Syc-Mazurek, Stephanie; Chen, John; Morris, Padraig; Sechi, Elia; Mandrekar, Jayawant; Tillema, Jan-Mendelt; Lopez, Alfonso; Lucchinetti, Claudia; Zalewski, Nicholas; Cacciaguerra, Laura; Buciuc, Marina; Krecke, Karl; et al.
Abstract : Objective: To determine the frequency of new/enlarging T2 or enhancing asymptomatic lesions in myelin-oligodendrocyte-glycoprotein-antibody-associated-disease (MOGAD) and compare to multiple sclerosis (MS) and aquaporin-4 antibody-positive-neuromyelitis-optica-spectrum-disorder (AQP4+NMOSD). Background: Data on new asymptomatic lesions in MOGAD is limited. Design/Methods: We retrospectively identified Mayo Clinic MOGAD patients with inclusion criteria of: 1)MOG-IgG positivity by live-cell-based-assay; 2)Fulfilling current MOGAD diagnostic criteria; 3) Baseline and follow-up paired MRIs without interval attacks. Paired MRIs (baseline and follow-up) were categorized as either attack-to-remission or remission-to-remission scans. A neurologist and neuroradiologist reviewed MRIs (T2-FLAIR brain, T2 spine, and T1-post-gadolinium brain and spine) to identify new/enlarging lesions. A subset of MOGAD patients matched for follow-up interval were compared to MS and AQP4+NMOSD patients. Results: We included 105 MOGAD patients (median age, 31 years[range, 3-80]; 60% female) with 373 paired MRIs (brain, 213, spine 160). In total, 13/373 (3%) scans (10/105 patients) had one or more new/enlarging T2-lesions (brain, 12/213[5.6%]; spine, 1/160[0.6%]) and 8/367 (2%) had enhancing lesions. New spinal lesions were rare across all groups (0-4%). T2 lesions occurred more commonly in attack-remission scans (8/171[4.7%]) then remission-remission scans (5/202[2.4%]). Clinical characteristics did not differ between patients who developed new/enlarging lesions and those who did not. Maintenance immunosuppressants were used in 44/105 (42%) patients. New/enlarging lesions did not predict future clinical relapse. New brain lesions were less in MOGAD (1/25[4%]) than MS (14/26[54%], p < 0.0001) but did not differ from AQP4+NMOSD (1/13[8%], p = 1.0) in subgroup analysis. Conclusions: New brain MRI lesions rarely develop outside of attacks in MOGAD which differs from MS. Surveillance MRI in MOGAD may have limited utility as a surrogate biomarker of disease activity in clinical practice and for clinical trials.